Evaluation of Glucokinase (Gck) rs4607517 Polymorphism Frequency and Nutritional Habits in Patients with Type 2 Diabetes - Nazan SON ERENOĞLU; Osman SON; Evrim Suna ARIKAN SÖYLEMEZ (The Avicenna Medical Journal, 2021)
Objectives/Background: The aim of this study was to investigate nutritional habits, biochemical markers and the allele and genotype frequencies of GCK rs4607517 -30G>A polymorphism of patients with Type 2 Diabetes Mellitus (T2DM).Methods:  The study was conducted with 200 T2DM patients and 100 controls. The analysis of GCK Gene rs4607517 -30G>A polymorphism was performed by Real-Time PCR method. The Attitude Scale for Healthy Nutrition was applied to the intervention group. Additionally, the sociodemographic data of the patients were collected, anthropometric measurements were performed and their biochemical markers were examined.Results: The mean duration of diabetes of the patients was 7.94±5.81 years, the mean age 55.88±12.23 years, the mean BMI 30.14±5.91 kg/m2, and the mean HbA1c value was 7.74±1.97. There was no difference between allele and genotype frequencies of two groups (p>0.05). The anthropometric and biochemical values of the patients with different genotype was similar (p>0,05). Furthermore, as the HbA1c values of the patients increased, the Malnutrition score was found to increase, and there was a statistically significant found between the groups (p=0.012). Conclusion: Although there are studies related to the effect of rs4607517 polymorphism in the GCK gene on the development of T2DM, the fact that the frequency of polymorphism of the patient group in our study was similar to the control group makes it necessary for the variant to be screened in larger patient populations. The majority of patients with T2DM were found to have high levels of HbA1c, LDL cholesterol, and triglycerides, inadequate level of nutrition knowledge and were obese.